Composite sodium p‐toluene sulfonate–polypyrrole–iron anode for a lithium‐ion battery. Issue 24 (20th February 2017) - Liao, Qishu; Hou, Hongying; Duan, Jixiang; Liu, Song; Yao, Yuan; Dai, Zhipeng; Yu, Chengyi; Li, Dongdong
ABSTRACT: In this study, p ‐toluene sulfonate (TsONa) doped polypyrrole (PPy) was synthesized for an anode in a lithium‐ion battery via a one‐step facile electropolymerization on Fe foil. The obtained TsONa–PPy–Fe composite electrode was investigated with scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, Fourier transform infrared spectroscopy, and galvanostatic charge–discharge profiling. As expected, many irregular microspherical particles of TsONa‐doped PPy formed and combined tightly with the surface of Fe foil. Furthermore, the obtained TsONa–PPy–Fe anode also delivered satisfactory electrochemical performances. For example, the reversible capacity was still about 105–115 mAh/g, even after at least 50 cycles. The high lithium storage activity of PPy and the high conductivity of the TsONa‐doped PPy jointly contributed into the satisfactory electrochemical performances. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44935. Abstract :